The limits of tradition peasants and land conflicts in Indonesia - Urano, Mariko (Kyoto area studies on Asia, 2010)
The Limits of Tradition explores the discourse of adat (customary or traditional) landownership that played an important role in peasant resistance against Indonesia's state development programs and demonstrates its inherent limits as a viable instrument for enhancing the rights of forest-dwelling communities. The book traces the process in which the Indonesian government, as well as NGOs, developed competing interpretations of the discourse, and it presents fieldwork reports on how the lower classes appropriated it. The Limits of Tradition represents an in-depth study on the role of subaltern elites in creating and organizing counter-hegemonic culture.